Pengembangan Sistem Rekomendasi Barbershop di Kota Malang yang Menerapkan Protokol Kesehatan Covid-19 - Muhammad Rifqi Ramdhani; Ratih Kartika Dewi; Tri Afirianto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
In this millennial era, self-care, especially in the hair area, is the main factor that is often considered by men in terms of appearance. Coupled with the rise of the barbershop business which is very much in demand by men today (Safa'at & Muttaqien, 2015). During this pandemic, people are worried and afraid when they want to cut their hair. The reason is the high rate of transmission of Corona Virus Disease (COVID-19) and the unexpected way of transmission. There are many barbershop locations in Malang City that are still open during this pandemic. Some of these places have complied with the health protocol following Decree of the Minister of Health Number HK.01.07/MENKES/382/2020 for hair care services and the like. However, some are still open even without complying with health protocols. Therefore, the development of a barbershop recommendation system is needed to assist users in choosing a barbershop in Malang City that applies health protocols. This recommendation system was developed using the Simple Additive Weighting method as a decision-making system. In the use of the SAW method, there are criteria used, namely distance, price, assessment, and the value of health protocols. The test for this barbershop recommendation system uses black-box testing to test the level of functionality with 100% valid results, then algorithm validation testing with a comparison of manual calculations that obtain 100% valid results, and usability testing with the System Usability Scale (SUS) approach by obtaining an average value of 77,5 or can be converted as Grade B in the Grade Scale category, Acceptable in the Acceptability Ranges category, and Good in the Adjective Rating category.